Perbandingan Pertumbuhan Butyrivibrio fibrisolvens E14 Varian Sticky dan Loose - Djarot Sasongko Hami Seno; John Douglas Brooker (Current Biochemistry, 2014)
A number of Butyrivibrio fibrisolvens strains have been reported to attach cellulose fibres, feed and other particles in the rumen, as well as to sheep rumen epithelia. In this research, B. fibrisolvens E14 variants sticky (S) and loose (L) were used to study the mechanism of B. fibrisolvens attachment to surfaces, especially to plant fibre. Results may be useful in enhancing plant fiber degradation within the rumen, or the use of plant biomass as energy source. The two cell types were compared; studies included physical and growth characteristics in defined, solid or liquid medium containing various carbon sources, the presence of compounds that may induce or inhibit attachment, and their phenotypic stability. Compared to the non-adhering L cells, the adhering S cells were shinier, spherical, more intensely pigmented (yellow), more firmly attached to the agar surface and could only be removed with scraping. After longer incubation, the cells were released from the agar but the colonies tended to stick together, and only became separable when further incubated. In contrast, the L cells were non spherical, loosely attached to the agar and separable at all stages of growth. In liquid medium, the S cells tended to clump during the early stages of growth, and be dispersed at later stages. The L cells were dispersed throughout the medium at all stages of growth. The phenotypes of the 2 variants were stable; both variants maintained their characteristics through multiple passages on solid and in liquid medium. The presence of molecules that induced attachment of S or inhibited attachment of L cells were not detected.